2017
DOI: 10.1038/oncsis.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA XIST increases blood–tumor barrier permeability and inhibits glioma angiogenesis by targeting miR-137

Abstract: Antiangiogenic therapy plays a significant role in combined glioma treatment. However, poor permeability of the blood–tumor barrier (BTB) limits the transport of chemotherapeutic agents, including antiangiogenic drugs, into tumor tissues. Long non-coding RNAs (lncRNAs) have been implicated in various diseases, especially malignant tumors. The present study found that lncRNA X-inactive-specific transcript (XIST) was upregulated in endothelial cells that were obtained in a BTB model in vitro. XIST knockdown incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 64 publications
2
94
0
Order By: Relevance
“…30 Furthermore, miR-26a inactivates the NF-κB signaling pathway by binding PRKCD mRNA and downregulates the levels of inflammatory chemokines CCL2 and CCL7, thereby suppressing the risk of DVT. 31 Subsequently, we found that overexpressed miR-103a-3p downregulated CXCL12 expression to reduce inflammatory response and thrombosis, which was verified by decreased IL-6, IL-8, and TF, PAIs, vWF, and TH-A2 expression in response to miR-103a-3p agomir injection in mice. Previous evidence has demonstrated that downregulation of certain inflammatory cytokines, including IL-6 and IL-8, is closely associated with alleviated inflammation in DVT.…”
Section: Mir-103a-3p Regulates Macrophage Polarization and Venous Tmentioning
confidence: 81%
See 1 more Smart Citation
“…30 Furthermore, miR-26a inactivates the NF-κB signaling pathway by binding PRKCD mRNA and downregulates the levels of inflammatory chemokines CCL2 and CCL7, thereby suppressing the risk of DVT. 31 Subsequently, we found that overexpressed miR-103a-3p downregulated CXCL12 expression to reduce inflammatory response and thrombosis, which was verified by decreased IL-6, IL-8, and TF, PAIs, vWF, and TH-A2 expression in response to miR-103a-3p agomir injection in mice. Previous evidence has demonstrated that downregulation of certain inflammatory cytokines, including IL-6 and IL-8, is closely associated with alleviated inflammation in DVT.…”
Section: Mir-103a-3p Regulates Macrophage Polarization and Venous Tmentioning
confidence: 81%
“…miR‐126, on the other hand, inhibits its target PIK3R2 gene expression, which acts to inhibit thrombus formation in vivo . Furthermore, miR‐26a inactivates the NF‐κB signaling pathway by binding PRKCD mRNA and downregulates the levels of inflammatory chemokines CCL2 and CCL7, thereby suppressing the risk of DVT …”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have been reported to be involved in a variety of biological processes, including tumorigenesis through regulating oncogenes or tumor suppressors at several levels (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). For example, Xia et al (13) demonstrated that long noncoding RNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) inhibited proliferation and invasion of glioma cells by suppressing the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, long non-coding RNAs (lncRNAs), newly identified members of the noncoding RNA family with length >200 nucleotides (nt), have been proposed (2)(3)(4). Accumulating documents have revealed that lncRNAs play a critical role in tumorigenesis and can be used as biomarkers for diagnosis or prediction of survival and recurrence in multiple cancers (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%